SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships